Enhancing Prehospital Outcomes for Cardiac Arrest (EPOC) study: sequential mixed-methods study protocol in Michigan, USA. Issue 11 (27th November 2020) - Salhi, Rama A; Fouche, Sydney; Mendel, Peter; Nelson, Christopher; Fetters, Michael D; Guetterman, Timothy; Forman, Jane; Nham, Wilson; Goldstick, Jason E; Lehrich, Jessica; Forbush, Bill; Iovan, Samantha; et al.
Abstract : Introduction: Out-of-hospital cardiac arrest (OHCA) is a common, life-threatening event encountered routinely by first responders, including police, fire and emergency medical services (EMS). Current literature suggests that there is significant regional variation in outcomes, some of which may be related to modifiable factors. Yet, there is a persistent knowledge gap regarding strategies to guide quality improvement efforts in OHCA care and, by extension, survival. The Enhancing Prehospital Outcomes for Cardiac Arrest (EPOC) study aims to fill these gaps and to improve outcomes. Methods and analysis: This mixed-methods study includes three aims. In aim I, we will define variation in OHCA survival to the emergency department (ED) among EMS agencies that participate in the Michigan Cardiac Arrest Registry to Enhance Survival (CARES) in order to sample EMS agencies with high-survival and low-survival outcomes. In aim II, we will conduct site visits to emergency medical systems—including 911/dispatch, police, non-transport fire, and EMS agencies—in approximately eight high-survival and low-survival communities identified in aim I. At each site, key informant interviews and a multidisciplinary focus group will identify themes associated with high OHCA survival. Transcripts will be coded using a structured codebook and analysed through thematic analysis. Results from aims I and II will inform the development of a survey instrument in aim III that will be administered to all EMS agencies in Michigan. This survey will test the generalisability of factors associated with increased OHCA survival in the qualitative work to ultimately build an EPOC Toolkit which will be distributed to a broad range of stakeholders as a practical 'how-to' guide to improve outcomes. Ethics and dissemination: The EPOC study was deemed exempt by the University of Michigan Institutional Review Board. Findings will be compiled in an 'EPOC Toolkit' and disseminated in the USA through partnerships including, but not limited to, policymakers, EMS leadership and health departments.